Năng lực hấp thụ vốn đầu tư trực tiếp nước ngoài của các tỉnh, thành phố trực thuộc Trung ương tại Việt Nam - Nguyễn Hồng , Sơn; Lý Đại , Hùng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
The paper assesses the foreign direct investment (FDI) absorption capacity by a cross-section regression method on a sample of 63 provinces and central cities in Vietnam over the 2010–2019 period. The FDI inflows improve for a higher economic growth rate, greater human resources, and better infrastructure. Compared with the FDI absorption capacity predicted by empirical model, Hanoi, Danang and Cantho still have available space to attract more FDI capital while Haiphong and Ho Chi Minh city have more FDI than forecasted value. Thus, the group of first three cities can upgrade the quality of strategic breakthroughs to attract more inflows of FDI while the group of two latter cities can transform to next stage of development based on the quality of FDI inflows. Among three strategic breakthroughs, upgrading the human resource needs to be a prioritised policy to attract more FDI in the provinces.